Ship That Held Up Wall Street. - Riess, Warren Curtis (Texas A & M University Press, 2014)
In January 1982, archaeologists conducting a pre-construction excavation at 175 Water Street in Lower Manhattan found the remains of an eighteenth-century ship. The Ship that Held Up Wall Street tells the whole story of the discovery, excavation, and study of what came to be called the "Ronson ship site," named for the site's developer, Howard Ronson. Entombed for more than 200 years, the Princess Carolina proved to be the first major discovery of a colonial merchant ship.